ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENANAMAN MODAL DALAM NEGERI (PMDN) DI SUMATERA BARAT - Desnim Silvia, Engla (Imara: JURNAL RISET EKONOMI ISLAM, 2018)
This paper aims to analyze the factors that influence domestic investment in West Sumatera. The type of research is descriptive and associative ones. The data were secondary and time series with a certain time period. Data were collected through literature studies, and analyzed descriptively and inductively by using multicollinearity test, heterokedasitas test, autokorelasi test, normality test, coefficient of determination (R2), multiple linear analysis, t test, and f test.   The findings of the research shows there is a significant influence between gross domestic regional products, security, and credit interest rates towards domestic investment in West Sumatera. It was obtained F hitung = 15,174 > F table = 3,49 and level sig = 0,000 < ? = 0,05. This show that gross domestic regional products, , security, and credit interest rates significantly effect the domestic investment in West Sumatera. It is recommended the government need to improve the securityby ensuring the safety of the investors' efforts from all crimes that have a direct or indirect impact on investors.